Spatial Pattern Analysis of the Distribution of Religious Services in the City of Ramadi Using Geographic Information Systems - الدليمي ياسر محمود حسن; شندوخ لؤي صلاح (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research included (analysis of spatial patterns of the location of religious services in the city of Ramadi using geographic information systems); in light of its spatial location for the year 2024, as the research highlighted (mosques), and dealt with two axes, the first axis is the spatial analysis of the location of mosques in the city of Ramadi, and it was found that there are (90) in all parts of the residential neighborhoods in the city of Ramadi, which number (33) residential neighborhoods located within the municipal borders of the cityAs for the second axis, which included the spatial statistical analysis of the location of mosques in the city of Ramadi using the Geographic Information Systems (GIS), it was concluded that the (Saleh Al-Hassan) Mosque, located in Al-Warar neighborhood, occupied the center of the studied phenomenon, located on the geographical coordinates X: 43°17’2.033"E)), Y: 33°25’36.25"N) when applying the geographical center tool in the ArcGis It was found that the location that was in the middle of all the studied phenomena of the mosques was near the Saleh Al-Hassan Mosque when applying the spatial average tool and the geographical coordinates (X: 43°17’17.444"E) (33°25’29.035"N), (Y:), (Y:; and when conducting statistical analysis of the distribution trend on mosques, we find that it showed a large spread in a specific direction starting from the eastern direction of the city, which is the center of Ramadi city, in the western direction of the city, and it also took part of the northern direction in its distribution, reaching the occupation of a large part of the southern direction, and the value of the rotation angle (Rotatio) = (30.493 degrees) The value of the nearest neighbor (neighborhood relation coefficient) - (Nearest Neighbor Reti) is (0.87). This indicates that the pattern of the signature of the mosques in the city of Ramadi is the (close/clustered) pattern that tends towards randomness. The total value of the standard score (Z-Score = -2.19) means that the pattern followed in the mechanism of distributing mosques in the study area falls within the range of the critical value (Value Critical) that ranges between (2.58-2.58). It is thus located within the acceptance area in its spatial distribution with a percentage of 99%; and the confidence level reached (P-Value = 0.02, which indicates a probability of (0%), i.e. less than (1%). This indicates that the mechanism for distributing mosques in the city of Ramadi, and the confidence level reached 99%.